Spatial dimensions of telemedicine and abortion access: a qualitative study of women's experiences - Katherine Ehrenreich; Cicely Marston (BMC, 2019)
Abstract Background Telemedicine may help women comply with onerous legislative requirements for accessing abortion services. In Utah, there are three mandatory steps: a state-mandated information visit, a 72-h waiting period, and finally the abortion procedure itself. We explored women's experiences of using telemedicine for the first step: the information visit. Methods We conducted 20 in-depth interviews with women recruited from Planned Parenthood Association of Utah in 2017 and analyzed them using iterative thematic techniques, using a framework based on Massey's conceptualization of space as comprising temporal, material and social dimensions. Results Temporal, material and social dimensions of women's access to abortion services intertwined to reduce access and cause discomfort and inconvenience among women in our sample. The 72-h waiting period and travel distance were the key temporal and material barriers, while social dimensions included fear of social judgement, religious influence, and negative stereotyping about people who have abortions. Women described traveling long distances alone and risking excessive pain (e.g. denying pain medication in order to drive immediately after the procedure) to try to overcome these barriers. Conclusion Using telemedicine helped patients reduce burdens created by policies requiring attendance at multiple appointments in a state with limited abortion services. Attending to spatial aspects of abortion provision helps identify how these different dimensions of abortion access interact to reduce access and impose undue burdens. Telemedicine can improve privacy, reduce travel expenses, and reduce other burdens for women seeking abortion care.